A GMCSF-Neuroantigen Tolerogenic Vaccine Elicits Systemic Lymphocytosis of CD4+ CD25high FOXP3+ Regulatory T Cells in Myelin-Specific TCR Transgenic Mice Contingent Upon Low-Efficiency T Cell Antigen Receptor Recognition - Moorman, Cody D.; Curtis, Alan D.; Bastian, Alexander G.; Elliott, Sarah E.; Mannie, Mark D. (Frontiers in Immunology, 2019)
Previous studies showed that single-chain fusion proteins comprised of GM-CSF and major encephalitogenic peptides of myelin, when injected subcutaneously in saline, were potent tolerogenic vaccines that suppressed experimental autoimmune encephalomyelitis (EAE) in rats and mice. These tolerogenic vaccines exhibited dominant suppressive activity in inflammatory environments even when emulsified in Complete Freund’s Adjuvant (CFA). The current study provides evidence that the mechanism of tolerance was dependent upon vaccine-induced regulatory CD25+ T cells (Tregs), because treatment of mice with the Treg-depleting anti-CD25 mAb PC61 reversed tolerance. To assess tolerogenic mechanisms, we focused on 2D2-FIG mice, which have a transgenic T cell repertoire that recognizes myelin oligodendrocyte glycoprotein peptide MOG35-55 as a low-affinity ligand and the neurofilament medium peptide NFM13-37 as a high-affinity ligand. Notably, a single subcutaneous vaccination of GMCSF-MOG in saline elicited a major population of FOXP3+ Tregs that appeared within 3 days, was sustained over several weeks, expressed canonical Treg markers, and was present systemically at high frequencies in the blood, spleen, and lymph nodes. Subcutaneous and intravenous administration of GMCSF-MOG were equally effective for induction of FOXP3+ Tregs. Repeated booster vaccinations with GMCSF-MOG elicited FOXP3 expression in over 40% of all circulating T cells. Covalent linkage of GM-CSF with MOG35-55 was required for Treg induction whereas vaccination with GM-CSF and MOG35-55 as separate molecules lacked Treg-inductive activity. GMCSF-MOG elicited high levels of Tregs even when administered in immunogenic adjuvants such as CFA or Alum. Conversely, incorporation of GM-CSF and MOG35-55 as separate molecules in CFA did not support Treg induction. The ability of the vaccine to induce Tregs was dependent upon the efficiency of T cell antigen recognition, because vaccination of 2D2-FIG or OTII-FIG mice with the high-affinity ligands GMCSF-NFM or GMCSF-OVA (Ovalbumin323-339), respectively, did not elicit Tregs. In conclusion, these findings indicate that GMCSF-MOG elicits Tregs by a mechanism contingent upon inefficient TCR-antigen recognition. Thus, the antigenic domain of the GMCSF-NAg tolerogenic vaccine is critical in setting the balance between regulatory and conventional T cell responses in both quiescent and inflammatory environments.